Learning from safeguarding adult reviews about Transitional Safeguarding: building an evidence base. Issue 2 (12th April 2022) - Preston-Shoot, Michael; Cocker, Christine; Cooper, Adi
Abstract : Purpose: The purpose of this paper is to set out the evidence base to date for Transitional Safeguarding to support authors of Safeguarding Adult Reviews (SARs) where Transitional Safeguarding is a key theme in the review. Design/methodology/approach: This paper draws on key evidence from several published sources about Transitional Safeguarding in England. This evidence is presented in this paper as a framework for analysis to support SAR authors. It follows the same four domains framework used in other adult safeguarding reviews: direct work with individuals; team around the person; organisational support for team members; and governance. This framework was then applied to two SARs written by two of the article's authors. Findings: The framework for analysis for Transitional Safeguarding SARs was applied as part of the methodology of two separate SARs regarding three young people. Key reflections from applying the framework to both SARs are identified and discussed. These included: providing an effective framework for analysis which all participants could use and a contribution for developing knowledge. Whilst many issues arising for safeguarding young people are similar to those for other adults, there are some unique features. The ways in which the gaps between children and adults systems play out through inter-agency and multi-professional working, as well as how "lifestyle choices" of young people are understood and interpreted are key issues. Practical implications: This paper presents an evidence base regarding Transitional Safeguarding for SAR authors who are tasked with completing a SAR where Transitional Safeguarding is a key theme. Originality/value: This paper draws together key literature and evidence about Transitional Safeguarding practice with young people. This paper argues that this framework for analysis provides SAR authors with a useful tool to support their analysis in this complex area of practice.